Iz zala Kostitutsionnogo suda . Iz zala Kostitutsionnogo suda . From the Constitutional Court . Из зала Конституционного суда - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the constitutional case on the constitutionality of the presidential decree suspending the activities of the CPSU and the Communist Party of the Russian Soviet Republic. Featured in the program: Pikhoia, Rudol'f Germanovich (Archivist); Shakhrai, Sergei Mikhailovich (Doctor of Juridical Sciences) Contributors: Menzelintsev, Igor' Borisovich (Anchor) Освещение рассмотрения Конституционным судом дела о конституционности указов президента Ельцина о приостановке деятельности КПСС и КП РСФСР. В программе участвуют: Пихоя, Рудольф Германович (Архивист); Шахрай, Сергей Михайлович (Доктор юридических наук) Создатели: Мензелинцев, Игорь Борисович (Ведущий/Ведущая)